Long-term decline in body condition of female Australian fur seals: potential causes and implications - Geeson, Johanna J.; Hindell, Mark A.; Hobday, Alistair J.; Speakman, Cassie N.; Arnould, John P. Y. (Frontiers in Marine Science, 2023)
The Australian fur seal (Arctocephalus pusillus doriferus, AUFS) population is still recovering from the over-exploitation of the commercial-sealing era (18th and 19th centuries). While the population is considered to be only < 47% of its pre-harvest size, it now represents the greatest resident marine predator biomass in the south-eastern Australian marine ecosystem. The region is experiencing rapid environmental change and, as a keystone predator species, the AUFS is an indicator of ecosystem health. In the present study, the body mass, standard length and body condition index (BCI) were analysed between 1997-2021 in adult female AUFS provisioning pups on Kanowna Island (northern Bass Strait), the third largest colony for the species. While substantial inter-annual fluctuations were observed, there was no temporal trend in standard length during the 23-year study period. In contrast, body mass and, consequently, BCI decreased significantly, suggesting the population is experiencing changing nutritional conditions. While these changes do not appear to be due to competition with commercial fisheries or population expansion, weak but significant negative relationships were observed between BCI and 1-year lagged sea surface temperature and summer zonal winds in the Bonney Upwelling region, and both current- and 2-year lagged Indian Ocean Dipole (IOD). These findings suggest the BCI of AUFS may continue to decline under predicted climate change conditions. While a lack of a concurrent decline in pup production could indicate a degree of nutritional tolerance or flexibility in energy allocation, further monitoring is required to assess decreases in reproductive parameters (e.g., birth mass, pre-weaning growth rates) or vital rates, which would be expected with continued nutritional stress.